Eksplorasi Gajut Manik-Manik Dalam Budaya Simalungun Pada Konsep Geometri - Anita Sabrina Pasaribu; Francius Sipayung; Hardi Tambunan; Ruth Mayasari Simanjuntak (Journal on Education, 2024)
Maths is the clearest and most unambiguous of sciences. However, for most students, mathematics is one of the most feared and difficult subjects to understand due to the lack of understanding of the concepts needed. In line with the mathematical concepts needed in learning, a teacher can relate mathematical concepts to local culture. Mathematics embedded in culture is called ethnomathematics. This research explores the concept of mathematics in Gajut Manik-manik. Gajut Manik-manik is part of the bride's outfit in Simalungun tradition which serves as a place for betel nut, areca nut, gambier, lime and tobacco. This study aims to explore the various mathematical concepts found in Gajut beads. The research method used is a qualitative method with an ethnographic approach. Data collection was done through observation, interviews, documentation, and literature study. The data collection instruments used were observation sheets, interview sheets, cameras, field notes and voice recorders. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The results obtained from this study indicate that there are mathematical concepts in Gajut beads, namely the concept of tube space, circle flat and kite. Thus, it can be concluded that Gajut beads can be used as a concrete mathematics learning tool in understanding mathematical concepts.